2015
DOI: 10.1007/s11064-015-1729-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection Against Diisopropylfluorophosphate in Acute Hippocampal Slices

Abstract: Diisopropylfluorophosphate (DFP) is an irreversible inhibitor of acetylcholine esterase (AChE) and a surrogate of the organophosphorus (OP) nerve agent sarin. The neurotoxicity of DFP was assessed as a reduction of population spike (PS) area elicited by synaptic stimulation in acute hippocampal slices. Two classical antidotes, atropine, and pralidoxime, and two novel antidotes, 4R-cembranotriene-diol (4R) and a caspase 9 inhibitor, were tested. Atropine, pralidoxime, and 4R significantly protected when applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…DFP has previously been employed to investigate the acute effects of an OP on the PS1, a response variable that can be directly correlated to the number of functional pyramidal cells in the stratum pyramidale of CA1 (Williamson and Sarvey, 1985;Jones et al, 1990;Ferchmin et al, 2015). Our results are consistent with these prior reports indicating acute DFP exposure inhibits CA1 glutamatergic transmission and that a substantial component of this inhibition is mediated via cholinergic receptors.…”
Section: Jpet # 263053supporting
confidence: 90%
See 2 more Smart Citations
“…DFP has previously been employed to investigate the acute effects of an OP on the PS1, a response variable that can be directly correlated to the number of functional pyramidal cells in the stratum pyramidale of CA1 (Williamson and Sarvey, 1985;Jones et al, 1990;Ferchmin et al, 2015). Our results are consistent with these prior reports indicating acute DFP exposure inhibits CA1 glutamatergic transmission and that a substantial component of this inhibition is mediated via cholinergic receptors.…”
Section: Jpet # 263053supporting
confidence: 90%
“…More specifically, following irreversible inhibition of AChE, enhanced synaptic ACh leads to hyperactivation of mAChRs, a well-established mechanism of OP-induced neurotoxicity (Abou-Donia et al, 2016). Previous studies have shown that mAChR blockade via ATR pretreatment partially prevents DFP-induced PS1 inhibition (Ferchmin et al, 2015). The present study showed that ATR pretreatment not only prevented DFP-mediated inhibition of the dH PS1 amplitude, but the amplitude was in fact significantly enhanced by DFP application.…”
Section: Jpet # 263053mentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco cembranoid diterpenes have excellent neuroprotective activity and could be used to develop drugs for the treatment of nerve damage caused by organophosphorus pesticides [36,37,38,39], Alzheimer’s disease and Parkinson’s disease [43,44,45,46]. Recent studies have shown that β-CBT-diol penetrates the blood–brain barrier to reach the brain to play a neuroprotective role, and pharmacokinetic studies of tobacco cembranoid diterpenes would accelerate the development of neuroprotective drugs [47].…”
Section: Bioactivities Of Tobacco Cembranoid Diterpenesmentioning
confidence: 99%
“…Notably, post-inflammatory 4R-treatment upregulated genes involved in inflammatory responses in peripheral macrophages after LPS. However, this did not translate into the propagation of cell damage in previously published in vivo experiments [9][10][11]14,15]. The post-inflammatory response to 4R could mean that 4R modulates inflammation in a manner that provides additional immediate support, but not prolonged enough to produce damage.…”
Section: R Treatment Alters Gene Expression In Murine Macrophages Rementioning
confidence: 87%